Conceptual underpinnings for transformative research in a service ecosystems context to resolve social issues – framework foundations and extensions. Issue 11 (10th September 2017) - Finsterwalder, Jörg; Foote, Jeff; Nicholas, Graeme; Taylor, Annabel; Hepi, Maria; Baker, Virginia; Dayal, Natasha
ABSTRACT: A number of services within society are designed to improve the well-being of its members and transform lives. Some services focus on the protection and support of vulnerable members of society, for example, those suffering the effects of drug use, mental health conditions, violence or poverty. Clients of such social services may also come from minority or marginalised cultural backgrounds. Typically, social services aim to reduce disparities and enhance individual and population well-being. A major challenge for social policy-makers and social service providers is to establish and maintain constructive engagement between the social services and those they are intended to serve. Some of these vulnerable clients are deemed 'hard-to-reach' (HTR) by policy-makers and service providers. Yet, the transformation of lives requires the involvement of the focal actor (client) and their service or activity system, as well as the engagement of other actors, such as the social worker embedded in their service or activity system. This paper aims to further unpack a novel approach, called integrative transformative service framework. This contribution extends its conceptualisation which fuses mainly three different approaches, namely Transformative Service Research (TSR), (Cultural-Historical) Activity Theory (CHAT) and (Regulatory) Engagement Theory (RET).